USING PROCEDURAL PARAMETERS AND CONTINUATIONS IN COMBINATORIAL SEARCHES - HWANG, WP; WANG, CL (My University, 1994)
We use procedural parameters as a means to cut off unwanted branches in a search tree. The technique may be used to effect non-blind backtracking. A recursive algorithm for generating all strings of n pairs of balanced parentheses is chosen as an illustrative example, since it cannot be formulated by conventional recursive backtracking.
Keywords: IMPERATIVE PROGRAMMING; PROCEDURAL PARAMETERS; CONTINUATIONS; PASCAL